Exports and Productivity: A survey of the evidence from firm level data - Joachim Wagner (Hamburg Institute of International Economics (HWWA), 2005)
While the role of exports in promoting growth in general, and productivity in particular, has been investigated empirically using aggregate data for countries and industries for a long time, only recently have comprehensive longitudinal data at the firm level been used to look at the extent and causes of productivity differentials between exporters and their counterparts which sell on the domestic market only. This paper surveys the empirical strategies applied, and the results produced, in 45 microeconometric studies with data from 33 countries that were published between 1995 and 2004. Details aside, exporters are found to be more productive than non-exporters, and the more productive firms self-select into export markets, while exporting does not necessarily improve productivity.
Keywords: D21; F14; 330; Exports; productivity; literature survey; micro data; Exportindustrie; Produktivität; Multinationales Unternehmen; Unternehmen; Welt